Detection of Static and Dynamic Stereopsis after Femtosecond Laser Small Incision Lenticule Extraction for High Myopia. (11th June 2021) - Xiang, Aiqun; Hang, Chu; Wu, Xiaoying; Yin, Yewei; Fu, Yanyan; Lu, Ying; Du, Kaixuan; Hu, Tu; Yan, Li; Wen, Dan
Abstract : Purpose . The purpose of this study is to test binocular visual function after femtosecond laser small incision lenticule extraction (SMILE) for high myopia. The traditional Titmus stereotest and dynamic stereotest based on the visual perception biological model were used for comparative analysis. Methods . A total of 43 patients were enrolled in this prospective study. At Week 1, Month 1, and Month 3 after surgery, the Titmus stereotest and dynamic stereotest generated by MATLAB were conducted. Dynamic stereopsis consists of randomly flickering Gabor spots and is divided into two models of high energy and low energy according to flicker frequency. Results . The preoperative manifest refraction spherical equivalent was −7.21 ± 0.70 D . The preoperative anisometropia was 0.52 ± 0.54D. The quartiles of static stereoacuity in preoperation and 3 follow-ups were as follows: 50.00 (25.00, 100.00) in preoperation, 63.00 (40.00, 63.00) at Week 1, 40.00 (32.00, 63.00) at Month 1, and 40.00 (25.00, 50.00) at Month 3. Static stereopsis improved at Month 1 and Month 3 compared with preoperation and Week 1 (P < 0.05 ). There were statistically significant differences in high energy dynamic stereopsis at Week 1 and Month 1 compared to preoperation (P < 0.05 ). In addition, significant differences in low energy dynamic stereopsis were detected between Month 1 and preoperation and also at Month 3 compared to Month 1 (P < 0.05 ). Conclusion . Most high myopia patients have a dynamic stereopsis deficiency before refractive correction. SMILE surgery can improve both static and dynamic stereopsis early in the postoperation period. However, in the long term, there is no significant difference or even a decrease in dynamic stereopsis.